How Artificial Intelligence is Revolutionizing Specialist Matching in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
How Artificial Intelligence is Revolutionizing Specialist Matching in Digital Health The journey to finding the right medical specialist can often be a ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning